An Analysis of Intra-ASEAN FDI Determinants in the Wake of ASEAN Economic Community - Ahmad Aswin Masudi (Center for Economic Studies Universitas Katolik Parahyangan, 2016)
This research intends to uncover the determinants of intra-ASEAN FDI, specifically to verify whether the establishment of ASEAN Economic Community has had any contribution to the raising intra-FDI inflow. Result from the fixed effect model with cross-section effects, which was employed to dataset of 10 ASEAN member states from 2000-2013, indicates that market size, quality of infrastructure, as well as labor productivity, were significant, and positively attracted intra-FDI inflow. Meanwhile, macroeconomic stability and degree of openness were insignificant. In addition, trade barrier was significantly proven to have negative effect on intra-FDI inflow. Unfortunately, the latest ASEAN’s investment scheme was insignificant. Moreover, the country-specific effects were highly significant, proving that heterogeneity seems to have an important role in attracting intra-ASEAN FDI. Keywords: intra-regional, foreign investment, economic integration, panel data.